Treatment of central serous chorioretinopathy with beta-blocker metipranolol - Chrapek, Oldrich; Jirkova, Barbora; Kandrnal, Vit; Rehak, Jiri; Sin, Martin (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2015)
AIM: The purpose of this study was to evaluate the effect of the systemically administered betablocker metipranolol on the course of central serous chorioretinopathy (CSC). METHODS: A prospective double-blind study involving 48 patients with a first attack of CSC not exceeding two weeks and who agreed to the follow-up ophthalmology examinations every week. The group was divided into a metipranolol group (n=23), receiving 10 mg of drug twice per day and a placebo group (n=25). The outcome measure was time in weeks from drug intervention (metipranolol vs. placebo) to reattachment of macula neuroepithelium. RESULTS: There was no statistically significant difference in duration of CSC in patients who used metipranolol and those who used placebo (P=0.341). CONCLUSIONS: In a prospective double-blind study, we found no effect of the betablocker metipranolol on the duration of central serous chorioretinopathy.
Keywords: výsledek terapie; Adrenergic beta-Antagonists; optická koherentní tomografie; Administration, Oral; zraková ostrost; metipranolol; následné studie; aplikace orální; vztah mezi dávkou a účinkem léčiva; Adult; Macula Lutea; Prospective Studies; dospělí; beta blokátory; centrální serózní chorioretinopatie; Visual Acuity; macula lutea; Follow-Up Studies; dvojitá slepá metoda; Treatment Outcome; lidé; ženské pohlaví; Humans; Tomography, Optical Coherence; Central Serous Chorioretinopathy; Double-Blind Method; Female; Dose-Response Relationship, Drug; Metipranolol; prospektivní studie